Does public reporting of the detection of fetal growth restriction improve clinical outcomes: a retrospective cohort study. (22nd December 2019) - Selvaratnam, RJ; Davey, M‐A; Anil, S; McDonald, SJ; Farrell, T; Wallace, EM
Abstract : Objective: To assess the impact of publicly reporting a statewide fetal growth restriction (FGR) performance indicator. Design: Retrospective cohort study from 2000 to 2017. Setting: All maternity services in Victoria, Australia. Population: A total of 1 231 415 singleton births at ≥32 weeks of gestation. Methods: We performed an interrupted time‐series analysis to assess the impact of publicly reporting an FGR performance indicator on the rate of detection for severe cases of small for gestational age (SGA). Rates of perinatal mortality and morbidity and obstetric intervention were assessed for severe SGA pregnancies and pregnancies delivered for suspected SGA. Main outcome measures: Gestation at delivery, obstetric management and perinatal outcome. Results: The public reporting of a statewide FGR performance indicator was associated with a steeper reduction per quarter in the percentage of severe SGA undelivered by 40 weeks of gestation, from 0.13 to 0.51% ( P = 0.001), and a decrease in the stillbirth rate by 3.3 per 1000 births among those babies ( P = 0.01). Of babies delivered for suspected SGA, the percentage with birthweights ≥ 10th centile increased from 41.4% ( n = 307) in 2000 to 53.3% ( n = 1597) in 2017 ( P < 0.001). Admissions to a neonatal intensive care unit for babies delivered for suspected SGA but with a birthweight ≥ 10th centile increased from 0.8 to 2.0% ( P < 0.001). Conclusions: The public reporting of an FGR performance indicator has been associated with the improved detection of severe SGA and a decrease in the rate of stillbirth among those babies, but with an increase in the rate of iatrogenic birth for babies with normal growth. Tweetable abstract: The public reporting of hospital performance is associated with a reduction in stillbirth, but also with unintended interventions. Tweetable abstract: The public reporting of hospital performance is associated with a reduction in stillbirth, but also with unintended interventions.